Avulsion of permanent teeth with open apex: a systematic review of the literature - Felipe G. Belladonna; Ane Poly; João M. S. Teixeira; Viviane D. M. A. Nascimento; Sandra R. Fidel; Rivail A. S. Fidel (Revista Sul-Brasileira de Odontologia, 2013)
Considered the most serious of dental inuries, avulsion is known as the total displacement of tooth out of its socket. Treatment includes immediate replantation and its success is directly related to several factors. Objective: This paper aimed to review the literature in a systematic way on dental avulsion of permanent teeth with open apex, covering various topics such as: reason for avulsion; storage media; time out of the socket; use of antibiotics; splinting time; tooth vitality; presence of resorption and/or obliteration of pulp canal; and following-up time. Material and methods: PubMed/MedLine database and Dental Traumatology journal were searched, from May to June of 2011, and several studies comprising the current and classic literature were listed using the following terms: tooth avulsion, open apex, permanent and case report. Results and conclusion: Twelve cases reports were selected. Cases of dental trauma in open apex teeth may have a good prognosis if the following steps are taken: the hydration of the tooth and immediately replantation. It is important to search dental care, even if everything seems solved, and the tooth following-up should be performed periodically as informed by the dentist.